2005
DOI: 10.1163/156853905774831873
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive social support in families of greylag geese (Anser anser)

Abstract: In general, support by social allies may reduce stress, increase success in agonistic encounters and ease access to resources. Social support was mainly known from mammals, particularly primates, and has been studied in birds only recently. Basically two types are known: (i) 'active social support', which describes the participation of a social ally in agonistic encounters, and (ii) 'passive social support' in which the mere presence of a social ally reduces behavioural and physiological stress responses. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 53 publications
1
58
1
Order By: Relevance
“…Coalitions for competition against conspecifics from other groups (hereafter 'group-wide coalitions') occur when the opponents belong to different social groups (or family units, e.g., Scheiber et al, 2005), whereas within-group coalitions occur when two or more members of the same group compete against at least one other 'ingroup' member. Group-wide coalitions can be offensive if individuals join forces to oust incumbent male(s) and take over a group (e.g., Pope, 1990;Rood, 1990;Packer et al, 1991;Waser et al, 1994;Ostner & Kappeler, 2004), or to conduct a lethal attack on members of a neighbouring group (reviewed by Wrangham, 1999;Wilson et al, 2014).…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
“…Coalitions for competition against conspecifics from other groups (hereafter 'group-wide coalitions') occur when the opponents belong to different social groups (or family units, e.g., Scheiber et al, 2005), whereas within-group coalitions occur when two or more members of the same group compete against at least one other 'ingroup' member. Group-wide coalitions can be offensive if individuals join forces to oust incumbent male(s) and take over a group (e.g., Pope, 1990;Rood, 1990;Packer et al, 1991;Waser et al, 1994;Ostner & Kappeler, 2004), or to conduct a lethal attack on members of a neighbouring group (reviewed by Wrangham, 1999;Wilson et al, 2014).…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
“…However, in this study, only four individuals from each brood were followed into winter. These four may have had strong associations with siblings and profited from their active or passive social support in aggressive encounters during the duckling period (Scheiber et al 2005). If these siblings were more subordinate and afterwards not present in the winter group, we cannot exclude the possibility that the re-arrangement of the social relationships among siblings between the duckling period and the early-winter phase was related to the change in the sibling-group composition between these two periods.…”
Section: Winter Social Relationshipsmentioning
confidence: 99%
“…Brood effects during winter could not be due to passive or active social support by the mother (Weiß and Kotrschal 2004) because mothers were not present during the second part of the experiment. Brood effects might be due to social support by siblings: dominant males may actively interfere in interactions involving their siblings or may tolerate the proximity of siblings more than that of unrelated individuals, having indirect consequences on their siblings' social rank (Scheiber et al 2005). Our present data do not allow the testing of this hypothesis.…”
Section: Brood Differencesmentioning
confidence: 99%
“…For intraspecific interactions, it is well documented that males are more aggressive and more dominant than females (e.g., Boyd 1953;Black and Owen 1987;Poisbleau et al 2006) and that families dominate pairs in aggressive encounters, whereas pairs tend to win against single individuals (e.g., Boyd 1953;Raveling 1970;Lamprecht 1986;Gregoire and Ankney 1990;Kotrschal et al 1993;Poisbleau et al 2006). Agonistic interactions within pairs or families are extremely rare (Boyd 1953;Scheiber et al 2009a), and members of a social unit actively and passively support each other in conflicts with other flock members (Weiß and Kotrschal 2004;Scheiber et al 2005Scheiber et al , 2009aScheiber et al , 2009b. Several studies further showed that family size affected rates of aggression as well as dominance rank (whitefronted geese, A. albifrons, Boyd 1953; snow geese, A. caerulescens, Gregoire and Ankney 1990; barnacle geese, Branta leucopsis, Loonen et al 1999), but such effects were absent in other studies (bar-headed geese, A. indicus, Lamprecht 1986; brent geese, B. bernicla, Poisbleau et al 2006;snow geese, Mulder et al 1995).…”
mentioning
confidence: 99%